The political economy of labor reform in Colombia (2004)
This paper analyzes the entire reformist effort that spans from 1990 until 2002, emphasizing the second wave that ended with the issuing of a new labor code in 2002. A successful reform has to surpass a set of "deals" along the streamline of design, consensus building within civil society, submission to Congress and parliamentary debate, before it gets approved. The paper presents the story of two failed attempts for producing these "deals" within the government, along with labor unions and private sector firm confederations, before the 2002 labor reform was finally enacted. It shows what economic and social considerations created the need for reform, describes the actual policy changes implemented and evaluates their impact. The paper delves deep into the political aspects of the reform effort. Public officials of two governments pursued different lines of reform, discussion strategies and mechanisms for creating consensus, before the initiative gained momentum and circumvented key obstacles. The text of the 2002 reform proposal changed little during five years, but received important additions in the floor of Congress, with little technical support. Finally, an interesting dispute between lawyers and economists is presented regarding the role of the labor code for job creation and its function in the economic cycle. In the case of this reform, economists believed more on the computed elasticities, while lawyers believed more in the stability of established rules and in the limited role of norms. Economists should pay more attention to the workings of the political economy of reform and to the "life cycle of government", both of them critical for success.